2010
DOI: 10.1002/ajmg.a.33300
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and emphysema in Williams–Beuren syndrome

Abstract: Williams-Beuren Syndrome (WBS) is caused by a submicroscopic deletion on chromosome 7q11.23 that encompasses the entire elastin (ELN) gene. Elastin, a key component of elastic fibers within the lung, is progressively destroyed in emphysema. Defects in the elastin gene have been associated with increased susceptibility towards developing chronic obstructive pulmonary disease (COPD) and emphysema in both humans and mice. We postulate that hemizygosity at the elastin gene locus may increase susceptibility towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…Because of the prevalent morbidity and mortality associated with the vascular disease in this condition, there has been less analysis of the effects of elastin haploinsufficiency on other elastic tissues. Case reports have noted emphysema, bladder, and colonic diverticuli, [Ignacio et al, 2012; Partsch et al, 2005; Sammour et al, 2006; Schulman et al, 1996; Wan et al, 2010] features potentially attributable to elastin insufficiency, and two studies have commented on the skin findings in the condition. Urban et.al.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the prevalent morbidity and mortality associated with the vascular disease in this condition, there has been less analysis of the effects of elastin haploinsufficiency on other elastic tissues. Case reports have noted emphysema, bladder, and colonic diverticuli, [Ignacio et al, 2012; Partsch et al, 2005; Sammour et al, 2006; Schulman et al, 1996; Wan et al, 2010] features potentially attributable to elastin insufficiency, and two studies have commented on the skin findings in the condition. Urban et.al.…”
Section: Introductionmentioning
confidence: 99%
“…While the paucity of reports of emphysema in WBS might suggest it as a rare complication of the disorder, the prevalence of lung involvement may be underestimated. For example, a survey of 16 adolescents and young adults with WBS found that 50% endorsed symptoms of shortness of breath, 43.8% reported cough, and 31.3% reported wheezing requiring medical treatment [Wan 2010]. Pulmonary imaging was not available as part of this study and it is possible that mild emphysema was present in some of these subjects.…”
Section: Discussionmentioning
confidence: 99%
“…There has been only one previously-reported case of emphysema in this syndrome [Wan 2010]. Here, we present a second adult patient with both WBS and emphysema.…”
Section: Introductionmentioning
confidence: 85%
“…In another study, the lungs of copper deficient rats developed emphysematous changes through defective cross linking between elastin and collagen due to decreased lysyl oxidase activity [15]. These findings indicate that dysfunctional elastin makes lung prone for emphysematous changes when exposed to injury/stress, with Wan et al [16] reporting on at least one lifelong nonsmoking adult patient with WBS who had moderate emphysematous changes on CT scan. They went on to perform spirometry on a small subset of young patients with WBS; although they did not demonstrate significant respiratory impairment they postulated that there was an anecdotally higher incidence of respiratory symptoms such as coughing and wheeze, perhaps due to subclinical emphysema and lung disease which may become more apparent at an older age.…”
Section: Discussionmentioning
confidence: 99%